2012
DOI: 10.1002/ajmg.c.31335
|View full text |Cite
|
Sign up to set email alerts
|

TRPV4‐associated skeletal dysplasias

Abstract: Dominant mutations in the TRPV4 gene result in a bone dysplasia family and form a continuous phenotypic spectrum that includes, in decreasing severity, lethal, and nonlethal metatropic dysplasia (MD), spondylometaphyseal dysplasia Kozlowski type (SMDK), and autosomal dominant brachyolmia. Several rare variant phenotypes that have some overlap but deviate in some ways from the general pattern have also been described. The known variant phenotypes are spondyloepiphyseal dysplasia Maroteaux type (Pseudo-Morquio t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
74
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(79 citation statements)
references
References 41 publications
(73 reference statements)
4
74
0
1
Order By: Relevance
“…15). Most of the mutations are gain-of-function mutations, and the degree of channel overactivity seems to determine the severity of the disease (Loukin et al, 2010a,b) (for reviews, see Nilius and Owsianik, 2010a;Nishimura et al, 2012;Nilius and Voets, 2013).…”
Section: Trp Channels As Drug Targetsmentioning
confidence: 99%
“…15). Most of the mutations are gain-of-function mutations, and the degree of channel overactivity seems to determine the severity of the disease (Loukin et al, 2010a,b) (for reviews, see Nilius and Owsianik, 2010a;Nishimura et al, 2012;Nilius and Voets, 2013).…”
Section: Trp Channels As Drug Targetsmentioning
confidence: 99%
“…Heterozygous mutations in this gene result in a spectrum of dominantly inherited SD phenotypes [3][4][5][6][7][8]. TRPV4 is a tetrameric calcium-permeable ion channel that plays a role in chondrocyte differentiation [9][10][11][12][13].…”
mentioning
confidence: 99%
“…However, reduced channel activity was reported for TRPV4 mutations in the mild disorder, familial digital arthropathybrachydactyly (FDAB), which is primarily characterized by osteoarthropathy in the hands [7]. TRPV4 mutations, sometimes in the same region of the gene, can show highly variable phenotypes that affect the skeleton, the peripheral nervous system, or both [6,8,13]. Several mechanisms for such phenotypes have been suggested, including: defects in Ca 2 + homeostasis in chondrocytes or in motor and sensory neurons, abnormal protein-protein interactions, or dysregulation of gene expression during chondrocyte differentiation [13].…”
mentioning
confidence: 99%
“…Recent studies revealed that mutations of TRPV4 are associated with varieties of skeletal dysplasia and osteoarthritis. 83 Different TRPV4 mutations cause dominantly inherited neurologic disorders such as congenital spinal muscular atrophy and hereditary motor and sensory neuropathy. Of interest, some patients with a TRPV4 mutation display skeletal dysplasia combined with peripheral neuropathy.…”
Section: Trpv4mentioning
confidence: 99%